2011
DOI: 10.3109/02770903.2011.631242
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Exercise-Induced Bronchospasm (EIB) and Asthma Control Test (ACT) in Asthmatic Children

Abstract: It must be stated that ACT alone is not sufficient to evaluate asthma control in children correctly because it fails to detect EIB in a significant percentage of subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…The lack of concordance between ACT results and AHR is in agreement with the literature [21,22], whereas there was no information or studies published about ATAQ.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The lack of concordance between ACT results and AHR is in agreement with the literature [21,22], whereas there was no information or studies published about ATAQ.…”
Section: Discussionsupporting
confidence: 85%
“…In particular, no studies have been carried out to study the same population with both questionnaires and comparing the two questionnaires with a validated stress test [21,22]. This is an important feature to investigate due to the fact that stress tests have been shown to be useful in evaluating asthma control and the efficacy of asthma therapy as indicated in the PRACTALL consensus [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results are in concordance with previous studies that showed no difference in pre‐exercise FEV 1 between EIB‐positive and negative groups . Although, asthmatics had diverse asthma control, supporting the previous studies, asthma control was not related to EIB. The exact pathology of EIB is still unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Rapino et al found a similar percentage of EIB in children with complete, partial or poor asthma control according to the ACT, i.e. 36% of children that report complete asthma control develop EIB during a treadmill exercise challenge [17]. Madhuban et al found no relationship between the categorical ACQ and the occurrence of EIB and a positive challenge test in 41% of asthmatic children reporting well-controlled asthma according to the ACQ [16].…”
Section: Discussionmentioning
confidence: 99%